Complex Korean Medicine Treatment after Elbow Replantation Following Traumatic Amputation: A Case Report - Eunbyul Cho; Shin-Hyeok Park; Hyesoo Jeon; Nam Geun Cho (MEDrang Inc., 2023)
Very few studies have been reported on upper extremity replantation following traumatic amputation. This case study aimed to report the progress of a patient treated with complex Korean medicine for 1 year after elbow replantation. The patient mainly complained of forearm sensory loss, muscle weakness, and hand pain after undergoing upper limb amputation and emergency replantation. He was hospitalized for approximately 50 days and then received outpatient treatment for approximately 10 months, followed by electroacupuncture, moxibustion, Chuna, herbal medicine, and transcutaneous electrical nerve stimulation. The muscle strength of the wrist joint improved to good (flexion) and fair (extension), and the forearm sensation was partially recovered approximately 10 months after the onset. To our knowledge, this is the first case report on replantation rehabilitation in Korean medicine, and it suggests that complex Korean medicine treatment might be beneficial for patients undergoing replantation after upper extremity amputation.